Tìm x, biết : (2x - 1)6 = 642
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 1:
a) \(8xy^2+24x^2y-32x^3y^2=8xy\left(y+3x-4x^2y\right)\)
b) \(x^2-16x-y^2+64=\left(x-8\right)^2-y^2=\left(x-8-y\right)\left(x-8+y\right)\)
Bài 2:
\(\left(x-4\right)^2-\left(12x+x^2\right)=6\)
\(\Rightarrow x^2-8x+16-12x-x^2=6\)
\(\Rightarrow20x=10\Rightarrow x=\dfrac{1}{2}\)
\(1,\\ =8xy\left(y+3x-4x^2y\right)\\ =\left(x-8\right)^2-y^2=\left(x-y-8\right)\left(x+y-8\right)\)
\(2,\Leftrightarrow x^2-8x+16-12x-x^2=6\\ \Leftrightarrow-20x=-10\\ \Leftrightarrow x=2\)
a. 523 – x = 301
x = 523 – 301
x = 222
b. x : 642 = 6
x = 642 x 6
x = 3 852
a: Ta có: \(2x\left(x-1\right)-2x^2=-6\)
\(\Leftrightarrow2x^2-2x-2x^2=-6\)
\(\Leftrightarrow x=3\)
b: Ta có: \(2x\left(x-3\right)+5\left(x-3\right)=0\)
\(\Leftrightarrow\left(x-3\right)\left(2x+5\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=3\\x=-\dfrac{5}{2}\end{matrix}\right.\)
0=(2x+1)2
4x2 + 4x + 1 = 0
4x2 = 0 hay 4x + 1 = 0
x = 2 hay x= \(-\dfrac{1}{4}\)
(2x+1)44=(2x+1)6
=> (2x+1)^4 - (2x+1)^6 = 0
=> (2x+1)^4 * [1 - (2x+1)^2] = 0
=> \(\left[{}\begin{matrix}\left(2x+1\right)^4=0\\\left[1-\left(2x+1\right)^2\right]=0\end{matrix}\right.\) \(\Leftrightarrow\) \(\left[{}\begin{matrix}2x+1=0\\\left(2x+1\right)^2=1\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}2x=1\\\left[{}\begin{matrix}2x+1=1\\2x+1=-1\end{matrix}\right.\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{1}{2}\\2x=0\\2x=-2\end{matrix}\right.\Leftrightarrow}\left[{}\begin{matrix}x=\dfrac{1}{2}\\x=0\\x=-1\end{matrix}\right.\)Vậy x\(\in\){0;-1;\(\dfrac{1}{2}\)}
\(a,\Leftrightarrow x^3-8-x\left(x^2-9\right)=1\\ \Leftrightarrow x^3-8-x^3+9x=1\\ \Leftrightarrow9x=9\Leftrightarrow x=1\\ b,\Leftrightarrow8x^3+12x^2+6x+1-8x^3 +12x^2-6x+1-24x^2+24x-1=0\Leftrightarrow1=0\Leftrightarrow x\in\varnothing\)
a) \(\Leftrightarrow x^3-8-x^3+9x=1\)
\(\Leftrightarrow9x=9\Leftrightarrow x=1\)
b) \(\Leftrightarrow8x^3+12x^2+6x+1-8x^3+12x^2-6x+1-24x^2+24x-6=5\)
\(\Leftrightarrow24x=9\Leftrightarrow x=\dfrac{3}{8}\)
Xét cấp số cộng 1, 6, 11, ..., 96.
Ta có: 96 = 1 + 5(n − 1) ⇒ n = 20
Suy ra
Và 2x.20 + 970 = 1010
Từ đó x = 1
(x+1)(2x-6)(2x^2+1)
=>
(x+1)(2x-6)(2x^2+1) = 0
=> x + 1 = 0 => x = -1
2x - 6 = 0 => x = 3
2x2 + 1 = 0 => x = -\(\sqrt{0,5}\)
làm bậy thui!!!
7867878998980
Ta có :
\(64^2=\left(4^3\right)^2=4^{3.2}=4^6\)
\(\Rightarrow\left(2x-1\right)^6=64^2\)
\(\Rightarrow\left(2x-1\right)^6=4^6\)
\(\Rightarrow2x-1=4\)
\(\Rightarrow2x=5\)
\(\Rightarrow x=2,5\)
(2x - 1)^6 = 64^2
(2x - 1)^6 = (4^3)^2
(2x - 1)^6 = 4^6
=> 2x - 1 = 4
2x = 4 + 1
2x = 5
x = 5 : 2
x = 2,5
Vậy x = 2,5